Discurso sobre a Pátria em O Cerro Largo durante a ditadura militar brasileira - Heinzmann, Yasmin Schreiner (2022)
In the present research, developed from the theoretical and methodological assumptions of materialist Discourse Analysis, we undertake a reflection on the constitution of the discourse about the Homeland during the period of the Brazilian military dictatorship (1964-1985), specifically in circulation in the press in the countryside, State of Rio Grande do Sul (RS). Thus, we aim to understand how the press managed to work, in that socio-historical and ideological moment, a certain memory about the Homeland, affiliated, above all, to the knowledge of Christian Religious Discursive Formation and Military Discursive Formation. For this purpose, we chose the newspaper O Cerro Largo, which circulated between 1957 and 1974, in the city of Cerro Largo, located in the countryside of the State of Rio Grande do Sul (RS) as an object of research. Through the newspaper editions, we designed the research corpus, consisting of nine discursive clippings that appear in the materialities in circulation, notably, in the sections alluding to the “Dia da Pátria” and the “Holiday of Tiradentes”, but we also focus on materialities which refer to the period of validity of the decree of Institutional Act N. 5 (AI-5), considered the most repressive of the military period. In light of this, our reflections permeate the ideological functioning of/in language, focusing on the production/movement of meanings about the Homeland during a period that is marked by the interdiction and repression of the subject's freedom. There is a memory, a discourse of, which returns and organizes the discourse about the Homeland, determining the events to be “celebrated” and put into circulation by the place of memory, the newspaper O Cerro Largo. On this threshold, we understand that the present research allows us to observe how the discourse about the Homeland was constituted in the newspaper, anchored in a memory, producing its variety, which is repeated, retaken, which stabilizes the senses, via a paraphrastic effect, in order to “throw out” of the subject discourse those meanings that were forbidden to the FDs considered dominant at the time. Furthermore, we explain the interdiscourse functioning, as pre- constructed, and the effect of the transverse discourse, which signal the ways in which these meanings about the Homeland return in the subject discourse, via the memory functioning, in the dictatorial production conditions.